The Analysis of Students’ Mathematical Reasoning Ability in Completing Mathematicalproblems on Geometry - Sandy, Widya Rizkha; Inganah, Siti; Jamil, Anis Farida (MEJ (Mathematics Education Journal), 2019)
This study aimed to describe the level of students' reasoning ability to solve the problems on flat sides of Geometry with the level of mathematical reasoning ability of high, moderate and low. The types and the research approaches used were descriptive qualitative and quantitative research design. The research subjectswere 6 students from class VIIIF. The form of data collection included 4 items ofwritten questions test and interview on the subject selected. Based on the analysis, the average value of the entire instrument about the mathematical reasoning abilities gained 71.5% for the indicators that carried out the calculations based on mathematical formulas or rules applicable. While 73.33% and 71.5% for the indicator of conclusions and 66.67% for the indicator ofestimation, that ifsummedup and averaged the percentage was 69%. The ability of class VIIIF students’ mathematical reasoning was fair.